Analisis strategi experiential marketing dalam mempengaruhi keputusan pembelian ulang minuman Staykult di Surakarta - Utomo, Fahman Hadi; Rachmawati, Sukma Amayliana (Nur Science Institute, 2022)
This study aims to find out what experiential marketing factors influence repurchasing decisions on sales of Staykult drinks in Surakarta and which experiential marketing factors are the most significant. The method used in this study is quantitative, with a multiple linear regression approach. The study results show that all Sense-Feel-Think-Act-Relate factors influence the repurchase decision. At the same time, the sense is the experiential marketing factor with the most substantial influence. The Staykult beverage shop stimulates the consumer's five senses by providing a taste in the form of drinks and food with a distinctive and high-quality taste, very comfortable room interiors, cleanliness, and excellent comfort. With fast service and the friendliness of the servers provided, customers feel comfortable in the shop to hang out with relatives for a long time, as a feeling that customers receive.